Contrasting 1D tunnel-structured and 2D layered polymorphs of V2O5: relating crystal structure and bonding to band gaps and electronic structure. Issue 23 (27th May 2016) - Tolhurst, Thomas M.; Leedahl, Brett; Andrews, Justin L.; Marley, Peter M.; Banerjee, Sarbajit; Moewes, Alexander
Abstract : An elucidation of structure–property relationships in V2 O5 polymorphs using synchrotron X-ray spectroscopy and density functional theory calculations. Abstract : New V2 O5 polymorphs have risen to prominence as a result of their open framework structures, cation intercalation properties, tunable electronic structures, and wide range of applications. The application of these materials and the design of new, useful polymorphs requires understanding their defining structure–property relationships. We present a characterization of the band gap and electronic structure of nanowires of the novel ζ-phase and the orthorhombic α-phase of V2 O5 using X-ray spectroscopy and density functional theory calculations. The band gap is found to decrease from 1.90 ± 0.20 eV in the α-phase to 1.50 ± 0.20 eV in the ζ-phase, accompanied by the loss of the α-phase's characteristic split-off d xy band in the ζ-phase. States of d xy origin continue to dominate the conduction band edge in the new polymorph but the inequivalence of the vanadium atoms and the increased local symmetry of [VO6 ] octahedra results in these states overlapping with the rest of the V 3d conduction band. ζ-V2 O5 exhibits anisotropic conductivity along the b direction, defining a 1D tunnel, in contrast to α-V2 O5 where the anisotropic conductivity is along the ab layers. We explain the structural origins of the differences in electronic properties that exist between the α- and ζ-phase.